2020
DOI: 10.1007/s11356-020-11499-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of the COVID-19 incidence pattern in Iran

Abstract: In the present paper, province-level variations of novel coronavirus (COVID-19) disease incidence across Iran were investigated. To this end, a geo-database from infected cases, deaths, total population, death-to-population ratio, and infected case-to-death ratio for 31 provinces of Iran and during seven successive periods of February 18–March 19 (P1), March 20–April 8 (P2), April 9–April 28 (P3), April 29–May 20 (P4), May 21–June 20 (P5), June 21–September 21 (P6), and September 22–October 21 (P7) of 2020 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
1
18
1
2
Order By: Relevance
“…In the present study, an 11.8% seroprevalence of COVID-19 was demonstrated in MS population at the beginning, which was much higher than the officially confirmed cases. The results were lower than a report in Iran on 8902 participants from the general population across 17 provinces, which revealed a total 17.1% seroprevalence of COVID-19 with a greater prevalence in Qom province (58.5%) ( Poustchi et al, 2021 ).However, amid the COVID-19 pandemic, regardless of the nationwide increasing trend of COIVD-19 prevalence and mortality in Iran ( Hazbavi et al, 2021 ), only 12.3% of MS patients developed COVID-19 which was significantly lower than general population. Moreover, the majority of MS patients (74.8%) developed mild COVID-19, and no death was reported.…”
Section: Discussioncontrasting
confidence: 57%
“…In the present study, an 11.8% seroprevalence of COVID-19 was demonstrated in MS population at the beginning, which was much higher than the officially confirmed cases. The results were lower than a report in Iran on 8902 participants from the general population across 17 provinces, which revealed a total 17.1% seroprevalence of COVID-19 with a greater prevalence in Qom province (58.5%) ( Poustchi et al, 2021 ).However, amid the COVID-19 pandemic, regardless of the nationwide increasing trend of COIVD-19 prevalence and mortality in Iran ( Hazbavi et al, 2021 ), only 12.3% of MS patients developed COVID-19 which was significantly lower than general population. Moreover, the majority of MS patients (74.8%) developed mild COVID-19, and no death was reported.…”
Section: Discussioncontrasting
confidence: 57%
“…The other research about spatial analysis was done by Franch-Pardo to review of the spatial analysis and Geographic Information System (GIS) to analyze of the Covid-19 level cases density by LQ method [15]. This result is in line with the research by Hazbavi, who conducting a spatio-temporal analysis of Covid-19 incidence at various locations in Iran, showed that there was a difference in the spatio-temporal pattern and the Location Quotient (LQ) index in most Iran's provinces having LQ>1 [17].…”
Section: Fig1: Map Of Distribution Case Per April Until December 2020supporting
confidence: 76%
“…The most frequently studied relationship of Covid-19 is related to meteorological factors and air pollutants as it influences coronavirus transmission, contributing to the spread of Covid-19 (Hazbavi et al 2020;Islam et al 2020). The majority of the studies relate temperature with Covid-19 cases and deaths and have mixed conclusions with positive/negative or no association between them.…”
Section: Literature Reviewmentioning
confidence: 99%